Desenvolvimento, caracterização e estudos da autofagia e apoptose em modelo celular de doença de Parkinson - Erustes, Adolfo Garcia [UNIFESP] (2018)
Parkinson’s disease (PD) is a chronic progressive disease characterized by the death of dopaminergic neurons in the substantia nigra pars compacta (SNpc) in the brain region. The main pathological feature of PD is the presence of cytoplasmic protein aggregates called Lewy Bodies, whose main component is the protein αsynuclein (αsyn). It is a protein with functions that remain poorly understood, however it might act in exocytosis of neurotransmitters vesicles and in regulation of mitochondrial physiology and morphology. This protein is predominantly found in wild type (WT) conformation, however mutations in the gene that encodes αsynuclein (SNCA) have been described as generating mutant species, such as A30P and A53T, both of which related to autosomal dominant cases of PD. The accumulation and aggregation of these proteins in the cytoplasm of neurons may cause mitochondrial dysfunction, cells stress, and cell death. Transglutaminase2 (TG2) is an enzyme that demonstrates an important role in the generation of protein aggregates in neurodegenerative diseases and mediates crosslink reactions of proteins. The aim of this work was to establish a neuronal cellular lineage overexpressing the αsyn (WT, A30P and A53T) and verify the occurrence mitochondrial dysfunctions, changes in mitochondrial membrane potential and Ca2+ homeostasis, as well as the mitochondrial accumulation of these proteins. For this purpose, western blot analysis, coimmunoprecipitation assays, as well as real time, space fluorescence, and confocal microscopy were used. The data showed that αsynucleins formed aggregates in cellular cytoplasm, mainly in the presence of TG2, and can mediate this process, by facilitating the oligomerization of these proteins. The aggregates were partially colocalized with mitochondria, affecting the mitochondrial membrane potential, deregulation in homeostasis, and mitochondrial Ca2+ accumulation. An increase in activation of the mitophagy pathway was also seen in cells overexpressing the mutants asyn A30P and A53T. In addition, the overexpression of αsyn promoted decrease in autophagic activity and the inhibition of protein degradation that causes accumulation of monomers and oligomers of αsyn. This data suggests that failures in protein degradation pathways influence the oligomerization and accumulation of αsyn; and that TG2, may also have some influence in this process. In addition, the cytoplasmic accumulation of αsyn affects mitochondrial physiology, mitochondrial membrane potential and interferes with Ca2+ homeostasis, especially in the presence of mutated αsyn A30P and A53T.